1999
DOI: 10.1182/blood.v94.6.1855.418k33_1855_1863
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Elements of vav Drive Transgene Expression In Vivo Throughout the Hematopoietic Compartment

Abstract: To develop a method for targeting expression of genes to the full hematopoietic system, we have used transgenic mice to explore the transcriptional regulation of the vav gene, which is expressed throughout this compartment but rarely outside it. Previously, we showed that a cluster of elements surrounding its promoter could drive hematopoietic-specific expression of a bacterial lacZ reporter gene, but the expression was confined to lymphocytes and was sporadically silenced. Those limitations are ascribed here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 35 publications
3
73
2
1
Order By: Relevance
“…To further analyze whether murine c‐FLIP R is indeed the functional counterpart of human c‐FLIP S in the immune system, we generated a mouse model overexpressing c‐FLIP R under the control of the vav ‐promoter, which has been described to induce expression in all hematopoietic cells . As expected, thymocytes, peripheral T cells and B cells from vavFLIP R mice were protected against CD95‐mediated apoptosis when induced by CD95L or by agonistic antibodies, but were sensitive to Dex‐induced cell death, which depends on the intrinsic, that is, mitochondrial, apoptosis pathway.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…To further analyze whether murine c‐FLIP R is indeed the functional counterpart of human c‐FLIP S in the immune system, we generated a mouse model overexpressing c‐FLIP R under the control of the vav ‐promoter, which has been described to induce expression in all hematopoietic cells . As expected, thymocytes, peripheral T cells and B cells from vavFLIP R mice were protected against CD95‐mediated apoptosis when induced by CD95L or by agonistic antibodies, but were sensitive to Dex‐induced cell death, which depends on the intrinsic, that is, mitochondrial, apoptosis pathway.…”
Section: Discussionmentioning
confidence: 88%
“…To address these questions, we analyzed endogenous c‐FLIP protein expression and show that murine c‐FLIP R is induced during T‐cell activation in a similar way as we previously reported for c‐FLIP S in the human system . Moreover, we generated vavFLIP R mice expressing a c‐FLIP R transgene under the control of the vav ‐promoter leading to expression in all hemato‐poietic cells . vavFLIP R mice had normal numbers and frequencies of immune cells in the steady state.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the identification of thrombopoietin (TPO) and development of primary megakaryocyte culture systems led to the observation that peak platelet production by mature megakaryocytes ‘corresponded to the onset of apoptosis’ (Zauli et al , ). When mice lacking the pro‐death BH3‐only protein BIM (Bouillet et al , ), or overexpressing pro‐survival BCL2 were found to be thrombocytopenic, the idea that megakaryocytes might undergo apoptosis deliberately in order to facilitate platelet shedding was born (Ogilvy et al , ).…”
Section: Megakaryocytes and Apoptosis: Productive Death?mentioning
confidence: 99%
“…Next, Pham et al (18) used the Vav1 oncogene promoter system first described by Ogilvy et al (19) to preferentially express either WT STAT5B or mutant STAT5B N642H in the hematopoietic compartment. They found that transgenic mice expressing human STAT5B N642H developed aggressive T cell leukemia/lymphoma (TLL) characterized by persistent tyrosine phosphorylation, increased numbers of myeloid progenitor cells, splenomegaly, and increased WBC counts, including expansion of CD8 + T cells.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%